A Child's Hidden Struggles: Self-Efficacy and Painful Feelings in the Years following Parental Separation. Issue 2 (17th February 2022) - Bell, Caitlin; Francia, Leanne; Millear, Prudence
ABSTRACT: The current study examined the influence of post-separation co-parental conflict on participants' self-efficacy and current distress, through the Cooperative-Competitive Parental Conflict Model. Participants were a community sample of 77 people who experienced parental separation as a child. Cooperative co-parenting was positively associated with good fathering, good mothering, and negatively associated with blaming father/mother for the separation, loss, and abandonment, and seeing life through the separation. Low self-efficacy, blaming mother, and acceptance of the separation predicted participant's current distress. The findings highlight the impact of post-separation co-parental conflict on children's self-efficacy and current distress.